The Diffusion of Digital Corporate Hegemony: Addiction, Capital and Discourse Power - Shitong Zhang (Journal of Linguistics and Communication Studies, 2023)
People are caught in social media, which digests their desires, and addiction has become a prominent phenomenon among users, but the platforms care nothing about the protection of users’ information and privacy, and their rights to express and choose. The collection and processing of user data by digital enterprises has undoubtedly become a new type of capital, which alienates individuals, affects the operation of social capital and political orientation, and how individuals defend their own boundaries has become an important issue.